Implementasi Kebijakan E-Learning dalam Meningkatkan Kualitas Pendidikan di Kota Surabaya - Mangkuto, Alfian Rajo; Widiyanto, Kendry (Universitas 17 Agustus 1945 Surabaya, 2019)
In accordance with the enactment of Law Number 20 of 2003 concerning the National education system in article 31 that distance education functions to provide educational services to groups of people who cannot attend face-to-face or regular education. With the development of existing technology at the moment, the Surabaya City Education Agency is innovating a policy in improving the quality of education in Surabaya. The policy innovation is an E-learning policy in the field of education. This e-learning policy has been formulated by the Surabaya City Education Office, and has been implemented at Junior High Schools in Surabaya. This study aims to describe the implementation of E-learning policies in improving the quality of education in Surabaya. This research uses descriptive qualitative research methods using observation techniques, in-depth interviews and relevant documents. From the results of this study note that the implementation of the E-learning policy is in accordance with the interests that influence the policy namely increasing academic and non-academic achievements in junior high schools in the city of Surabaya. The results of this study are connected with the theory of Merilee S Grindle which has 2 indicators, namely the contents of the policy and the policy environment.Keyword : Policy Implementation, E-learning.